Impacts of extreme environmental disturbances on piping plover survival are partially moderated by migratory connectivity. (December 2021) - Ellis, Kristen S.; Anteau, Michael J.; Cuthbert, Francesca J.; Gratto-Trevor, Cheri L.; Jorgensen, Joel G.; Newstead, David J.; Powell, Larkin A.; Ring, Megan M.; Sherfy, Mark H.; Swift, Rose J.; Toy, Dustin L.; Koons, David N.
Abstract: Effective conservation for listed migratory species requires an understanding of how drivers of population decline vary spatially and temporally, as well as knowledge of range-wide connectivity between breeding and nonbreeding areas. Environmental conditions distant from breeding areas can have lasting effects on the demography of migratory species, yet these consequences are often the least understood. Our objectives were to 1) evaluate associations between survival and extreme environmental disturbances at nonbreeding areas, including hurricanes, harmful algal blooms, and oil spills, and 2) estimate migratory connectivity between breeding and nonbreeding areas of midcontinental piping plovers ( Charadrius melodus ). We used capture and resighting data from 5067 individuals collected between 2002 and 2019 from breeding areas across the midcontinent, and nonbreeding areas throughout the Gulf of Mexico and southern Atlantic coasts of North America. We developed a hidden Markov multistate model to estimate seasonal survival and account for unobservable geographic locations. Hurricanes and harmful algal blooms were negatively associated with nonbreeding season survival, but we did not detect a similarly negative relationship with oil spills. Our results indicated that individuals from separate breeding areas mixed across nonbreeding areas with low migratory connectivity. Mixing among individuals in the nonbreeding season may provide a buffering effect against impacts of extreme events on any one breeding region. Our results suggest that understanding migratory connectivity and linking seasonal threats to population dynamics can better inform conservation strategies for migratory shorebirds.